Competence in Streptococcus pneumoniae and Close Commensal Relatives: Mechanisms and Implications - Salvadori, Gabriela; Junges, Roger; Morrison, Donald A.; Petersen, Fernanda C. (Frontiers in Cellular and Infection Microbiology, 2019)
The mitis group of streptococci comprises species that are common colonizers of the naso-oral-pharyngeal tract of humans. Streptococcus pneumoniae and Streptococcus mitis are close relatives and share approximately 60 to 80% of orthologous genes, but still present striking differences in pathogenic potential towards the human host. S. mitis has long been recognized as a reservoir of antibiotic resistance genes for S. pneumoniae, as well as a source for capsule polysaccharide variation, leading to resistance and vaccine escape. Both species share the ability to become naturally competent, and in this context, competence-associated killing mechanisms such as fratricide are thought to play an important role in interspecies gene exchange. Here, we explore the general mechanism of natural genetic transformation in the two species and touch upon the fundamental clinical and evolutionary implications of sharing similar competence, fratricide mechanisms, and a large fraction of their genomic DNA.